Regulation of piglet T-cell immune responses by thioredoxin peroxidase from Cysticercus cellulosae excretory-secretory antigens - He, Wei; Sun, Xiaoqing; Luo, Bo; Liu, Meichen; Li, Lizhu; Fan, Xianmin; Ye, Jingming; Zhou, Biying (Frontiers in Microbiology, 2022)
Cysticercosis is a serious threat to human health and the development of animal husbandry. During parasitization, Cysticercus cellulosae (C. cellulosae) can excrete or secrete antigens that modulate the host's T-cell immune response. However, the composition of C. cellulosae ESAs is complex. In order to find the key molecules involved in regulating T cell immune response in C. cellulosae ESAs, we screened the thioredoxin peroxidase (TPx) with the highest differential expression as the key target by label-free quantification (LFQ) proteomics of C. cellulosae and its ESAs, and verified that TPx protein mainly exists in C. cellulosae ESAs. The TPx recombinant protein was prepared by eukaryotic expression, and ESAs were used as the experimental group control to further investigate the effect of TPx protein on the immune response of piglet T cells. TPx protein induced an increase in the number of CD4+ T cells in the peripheral blood (PBMCs) of piglets, while the number of CD8+ T cells did not change significantly, resulting in an imbalance in the ratio of CD4+/CD8+ T cells, and an increase in the number of CD4+CD25+Foxp3+ Treg cells in the PBMCs. In addition, TPx protein could initiate the Th2-type immune responses by secreting IL-4 and IL-10, and suppresse the Th1/Th17-type immune responses. The results show that ESAs were involved in regulating the immune response of piglet T cells, and it may be that TPx protein among ESAs components play one of the major roles, thus evading host immune attack, laying a foundation for the subsequent exploration of How TPx protein regulates signaling molecules to influence T cell differentiation.